MONO-ECONOMY AND ITS IMPLICATIONS FOR DELTA STATE OF NIGERIA - EBHODAGHE, Isaac Ighodalo; OSIMERAH, Charles Aleonokhua; BOUBAI, Joseph Jackson (EBSU Journal of Social Sciences and Humanities, 2022)
The study examines mono-economy and its implications for Delta State of Nigeria. Thus, the specific objectives were to: find out how agricultural products enhance the economy of Delta State; examine the over reliance on petroleum products (mono-economy) and its implication for the agricultural sector of Delta State and; investigate the consequences of mono-economy for Delta State. To achieve these, the study employed the system theory as a tool of analysis. It adopted the qualitative methods, using historical research design, and relied essentially on secondary data; sourced from archives, texts, journal articles, newspapers, monographs, magazines, and relevant web pages. The research study unveiled a paradox, noting a situation where petroleum products exported in large quantity and benefits from agriculture that supposed to be a blessing to Nigeria and Delta State in particular, has turned out to be a curse due to corruption perpetrated by both the military and political leaders. The implication for Delta State is that payment of the salaries of civil servants, teachers and other workers became cumbersome, not to disclose the mass unemployment and lack of infrastructural development, which leads to crimes, such as kidnapping, and armed robbery in the State, and Nigeria at large. The study therefore recommend amongst others the urgent need for the Buhari administration and the prospective successor to carry out fresh policies and measures to encourage a rapid diversification of Nigerian economy, Delta State in particular away from its current over-dependence on oil and gas sector.